Prevalence and incidence of frailty among community-dwelling older adults in Slovenia - Jazbar Janja; Pišek Špela; Locatelli Igor; Kos Mitja (Sciendo, 2021)
Frailty is recognized as one of the most important global health challenges as the population is aging. The aim of this study was to evaluate prevalence and incidence of frailty, and associated factors, among the population of older adults in Slovenia compared to other European countries.